1984
DOI: 10.1073/pnas.81.8.2359
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the magnetic properties of deoxy- and photodissociated myoglobin.

Abstract: The magnetic susceptibility of photodissociated carbon monoxy myoglobin has been measured over the temperature range from 1.7 to 25 K at 10 and 50 kG with a superconducting susceptometer. The spin and the crystal field parameters of the iron ion were extracted by a spin Hamiltonian approach. Under equivalent conditions the magnetic susceptibility of deoxy myoglobin was measured. In both experiments the CO-bound protein was used as a diamagnetic reference. Above about 5 K the metastable photolysed state and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…The spectra ofthe photoproduct at low temperatures reported here are characteristic of high-spin five-coordinate hemes, consistent with other studies that have also shown that the iron atom in the photoproduct is high spin (S=2) (11). We conclude that the photoproduct generated at very low temperatures (1.6 and 4 K) has a high-spin heme that is slightly perturbed compared to the heme in the equilibrium deoxy preparation.…”
Section: Discussionsupporting
confidence: 78%
“…The spectra ofthe photoproduct at low temperatures reported here are characteristic of high-spin five-coordinate hemes, consistent with other studies that have also shown that the iron atom in the photoproduct is high spin (S=2) (11). We conclude that the photoproduct generated at very low temperatures (1.6 and 4 K) has a high-spin heme that is slightly perturbed compared to the heme in the equilibrium deoxy preparation.…”
Section: Discussionsupporting
confidence: 78%
“…13. The parameter set, which now invokes a spread in parameters D and E, is compatible with magnetic susceptibility (40) and far-infrared (22) results. However, the Mb spectra are similar to those of the hexaquo Fe+2 and FeTPP with the trough in dx'"/dB for Mb occurring 5 mT higher and being approximately a factor of three weaker than in the FeSO, spectra of Fig.…”
Section: Myoglobin (Mb)supporting
confidence: 61%
“…The exciting features of this structure were (1) the ligand was located in the heme pocket 3-4 Å from the iron atom essentially parallel to the heme and (2) the proximal histidine-iron coordinate had moved close the deoxy structure but was essentially relaxed only 75% toward the deoxy coordinates. This provided reasonable structural interpretations for both the infrared signature of the B states, which are close to the free gas value of the CO stretching frequency (Alben et al, 1982;Ansari et al, 1987), and the high-spin (S ) 2), outof-plane spectroscopic assignment for the iron atom based on optical, Mossbauer, magnetic susceptibility, and X-ray absorption spectroscopy (XAS) data (Chance, 1993;Iizuka et al, 1974;Marcolin et al, 1979;Miller & Chance, 1995;Roder et al, 1984;Spartalian et al, 1976). In addition, recent time-resolved photoselection spectroscopy experiments have provided additional details about the CO ligand geometry in the bound state and its trajectory upon photolysis (Lim et al, 1995).…”
mentioning
confidence: 93%